When Clients Have Questions: A Guide for Professional Pesticide Applicators - Frederick M. Fishel (EDIS, 2006)
PI-124, a 3-page fact sheet by Frederick M. Fishel, addresses situations that professional pesticide applicators should take into account when interacting with those who don't have a working knowledge of professional pesticide application. Published by the UF Pesticide Information Office, June 2006.